2014
DOI: 10.11114/ijsss.v2i2.287
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Sex with Cerebral Palsy: A Phenomenological Exploration of Private Constructions of Sexuality Using Sexual Script Theory

Abstract: This study explored how people with cerebral palsy (CP) negotiated and perceived their sexual interactions with others. In doing so, this research discusses participant conceptualizations of sexuality with CP. In-depth, semi-structured interviews were conducted with two women and five men with moderate to severe cerebral palsy from Canada and Australia. The interview discourse focused on how, if at all, private/internal constructions of sexuality influenced the way in which participants expressed and negotiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In terms of disabled sexualities specifically, Shakespeare (2000) believes neglecting impairment obscures both the real physiological issues that disabled people experience, as well as differences between people with disabilities that stem from different types of impairments. Such differences have been noted by Dune (2014) who found that those with cerebral palsy often felt others with more severe physical disabilities, like spinal cord and degenerative musculoskeletal diseases, carried more sexual stigma and had less normative sexual function than they had, which was a contributing factor to more positive body image in those with cerebral palsy.…”
Section: As Shakespeare Arguesmentioning
confidence: 82%
“…In terms of disabled sexualities specifically, Shakespeare (2000) believes neglecting impairment obscures both the real physiological issues that disabled people experience, as well as differences between people with disabilities that stem from different types of impairments. Such differences have been noted by Dune (2014) who found that those with cerebral palsy often felt others with more severe physical disabilities, like spinal cord and degenerative musculoskeletal diseases, carried more sexual stigma and had less normative sexual function than they had, which was a contributing factor to more positive body image in those with cerebral palsy.…”
Section: As Shakespeare Arguesmentioning
confidence: 82%
“…While bound to our individual identities, we are also bound to our communal realities (Dune, 2014 ). It was therefore important, informative, and cathartic to immerse ourselves in the narratives of the other authors, allowing each of our narratives to speak to and inform each other, thus the additional need to adopt a collaborative auto‐ethnographic approach (Chang et al., 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…Public influences were cumulatively the second most important factor in the construction of sexuality by people with cerebral palsy (Dune, 2014b). Finally, private influences were cumulatively the least influential factor in the construction of their sexuality (Dune, 2014a). Sexual spontaneity primarily was a derivative of sexual exploration.…”
Section: Sexualitymentioning
confidence: 99%